DRUG SCENE CHANGES DURING TWO DECADES: SLOVAKIA 1993 – 2012 - Nociar, Alojz (European Scientific Journal, ESJ, 2013)
Study presents short overview of drug situation’s indicators during the first, or heroin decade of drugs, and then during the second, soft and synthetic drugs decade of drugs in Slovakia. Then the results of series of nation-wide school surveys, mapping development of licit and illicit drugs use among children and youth during nineties are outlined. The results indicated constant growth of licit and illicit drugs consumption among primary school pupils, and secondary school students until the fourth wave of nation-wide school surveys in the years 2006 – 2007. However, the next wave after four years has detected profound change in the expected pattern of further growth in the case of illicit drugs. Instead of this decline of use or at least stabilization occurred among Slovak youth. At the same time we have found growth of use in the case of licit drugs – alcohol and tobacco, more profoundly among girls. Also the use of new synthetic drugs among young people was revealed via traditional school survey.